A STUDY EXAMINING THE ATTITUDE OF UAE VOCATIONAL INSTITUTES GRADUATING STUDENTS TOWARDS ENTREPRENEURSHIP - Sumbul, Maria; Faisal, Mirha (PEOPLE: International Journal of Social Sciences, 2018)
Entrepreneurship is important for the economy’s growth especially in the current time of recession. This paper aims to examine the attitude of graduating students of UAE vocational institutes towards entrepreneurship and also assess its influencing factors. Research highlights the ratio of graduating student intending to start their own business as the majority of Middle East population is expats and family businesses are considered to be very important in Middle Eastern economies, contributing 60% to GDP and employing over 80% of the workforce (Middle East Family Business Survey, 2016). By applying Multivariate regression analysis on the data collected from 4 vocational institutes across UAE through structured questionnaire; it is found that family experience has a significant impact on the positive attitude of graduates towards entrepreneurship. The surprising finding of this paper is that in spite of positive attitude of graduate towards entrepreneurship, their enterprise knowledge is low. Results are encouraging for future studies to compare the entrepreneurial attitude for different nationalities in private and public sector. As there is less support from institutions for entrepreneurs, the findings of this research would be beneficial for the academic institutions and government to strategise initiatives for their easy access to training and financial aid.